MENTORING AND TRAINING ON BUSINESS PLAN PREPARATION: CAMPUS ROADSHOW COLLABORATION WITH DIPLOMAT SUCCESS CHALLENGE - Muhammad Arif Rakhman; Nurmiyati, Nurmiyati; Khasanah, Uswatun (Jurnal Indonesia Mengabdi, 2024)
One of the keys to successfully starting a business is the ability to express brilliant ideas or insights that are creative and innovative and have high economic/commercial value into a proper and realistic business plan. One of the efforts that can be carried out to improve student competence is to prepare a business plan through training and mentoring. This community service activity (PKM) is a systematic service activity, namely a team of lecturers from Undaris Kab. Semarang collaborating with Diplomat Success Challenge (DSC). PKM activities are carried out using the PAR (Participatory Action Research) method. The total number of participants was 183 students. The stages carried out in this service are the planning stage, the implementation stage (presentation of material by the speakers, discussions, work practices), and the evaluation stage. The results of the service found that participants were able to take part in interactive activities, some participants were able to compile business plan proposals and submit their proposals via the web at https://www.diplomatsukses.com/; and participants were very satisfied with the activities carried out. Further recommendations are to be carried out more intensively and target participants more broadly in the form of training and mentoring activities.